The rise of civil society groups in Africa - André-Michel Essoungou (Africa Renewal, 2013)
Under the glaring sun of a recent Monday, an unusual group of protesters marched on the streets of Kampala, Uganda’s capital, all dressed in black “to mourn the loss of Uganda’s public money through corruption,” as some of them pointedly explained to reporters. “Return our money and resign,” read one of the slogans they brandished. Since November 2012, on the first Monday of each month, the Black Monday Movement—a coalition of local NGOs and civil society groups—has taken to the streets to highlight the effects of corruption in Uganda and to press public officials to act.